Formulasi Dan Evaluasi Sediaan Blush On Cream Kombinasi Ekstrak Kelopak Bunga Rosela (Hibiscus sabdariffa L.) Dan Umbi Wortel (Daucus carota L.) - Riza Dwiningum; Mida Pratiwi; Wina Safutri; Rinda Agustin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The cosmetic industry in Indonesia continues to grow rapidly, particularly in products like blush on, which are used to enhance facial appearance. However, the use of synthetic colorants such as rhodamine B in cosmetics poses health risks, and is therefore prohibited by BPOM. As a safer alternative, natural colorants are used, such as extracts of roselle petals (Hibiscus sabdariffa L.) and carrot tubers (Daucus carota L.), which provide both coloring effects and antioxidant benefits due to their β-carotene content. This research aims to formulate and evaluate blush on cream made with these natural colorants. It is an experimental laboratory study that evaluates the physical characteristics and user preferences for blush on cream formulations using a combination of roselle and carrot extracts. Three formulas were developed with a constant roselle extract concentration of 0.5% and varying carrot extract concentrations of 10% (F1), 30% (F2), and 50% (F3). Evaluations included organoleptic properties, pH, homogeneity, viscosity, spreadability, adhesiveness, pigment stability, product stability, protection ability, and hedonic tests. The results showed that the colors produced were peach, orange-red, and bright orange, depending on the carrot concentration. All formulas met the standard requirements across the tested parameters. Formula 2 is the most optimal and generally preferred overall, as it has a balanced aroma, an appealing color, and a soft texture. In the preference test, it showed the best blush-on cream results from the combination of roselle extract and varying concentrations of carrot.